Blow-Up of Solutions for a Class Quasilinear Wave Equation with Nonlinearity Variable Exponents. (15th May 2021) - Tebba, Zakia; Degaichia, Hakima; Abdalla, Mohamed; Cherif, Bahri Belkacem; Mekawy, Ibrahim
Abstract : This work deals with the blow-up of solutions for a new class of quasilinear wave equation with variable exponent nonlinearities. To clarify more, we prove in the presence of dispersion term − Δ u t t a finite-time blow-up result for the solutions with negative initial energy and also for certain solutions with positive energy. Our results are extension of the recent work (Appl Anal. 2017; 96(9): 1509-1515).